If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying lg(8x + 3) = 1 Reorder the terms: gl(3 + 8x) = 1 (3 * gl + 8x * gl) = 1 (3gl + 8glx) = 1 Solving 3gl + 8glx = 1 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Reorder the terms: -1 + 3gl + 8glx = 1 + -1 Combine like terms: 1 + -1 = 0 -1 + 3gl + 8glx = 0 The solution to this equation could not be determined.
| 2(x-3)+5=-4(2x-1) | | 3-4(x-5)=3x+6(x-3) | | R+48=7c | | Q=7-2p | | 10=4d+2 | | 2.4x+7.2=-62.4 | | 2(-5)-3(3/4)-(6) | | 2lx-6l=48 | | f(x)=x^4-3x^2+5 | | 25x+2y-19x-1y= | | 4x^2+25y^2-50y=75 | | -7.9d+7.7=274.72 | | (-5)(6)(1/3) | | -7d+7.7=274.72 | | 5p-2=3/4 | | -3(x-1)+9=3 | | 5+3h=17 | | (2x-3)+5=-4(2x-1) | | n+23445566776554544=23445566776554544 | | m/-3=2 | | -u+9=32.9 | | T-(-1)=(-5) | | L=-5t^2-8t+120 | | 2X^2+3X+7=2 | | x^2+8x+15=63 | | n-23445566776554544=23445566776554544 | | 3(x-7)-2(2x+4)=7 | | 4x+x+-2x+3=54 | | 7r-3=-309.6 | | 32-6x=11-9x | | 6x^2+1.5x+2=0 | | f/3-15=-12 |